2019
DOI: 10.2147/dddt.s215895
|View full text |Cite
|
Sign up to set email alerts
|

<p>Glucoside Derivatives Of Podophyllotoxin: Synthesis, Physicochemical Properties, And Cytotoxicity</p>

Abstract: BackgroundWidespread concern of the side effects and the broad-spectrum anticancer property of podophyllotoxin as an antitumor agent highlight the need for the development of new podophyllotoxin derivatives. Although some per-butyrylated glucosides of podophyllotoxin and 4β-triazolyl-podophyllotoxin glycosides show good anticancer activity, the per-acetylated/free of podophyllotoxin glucosides and their per-acetylated are not well studied.MethodsA few glucoside derivatives of PPT were synthesized and evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…It has also been noted for its cytotoxic activity in other human cancer cell lines, HL-60, SMMC-7721, A-549, and SW480 (Zi et al. 2019 ). Podophyllotoxin and its derivatives exhibit anticancer activity, mainly due to its ability to inhibit tubulin polymerisation into microtubules (Kamal et al.…”
Section: Discussionmentioning
confidence: 93%
“…It has also been noted for its cytotoxic activity in other human cancer cell lines, HL-60, SMMC-7721, A-549, and SW480 (Zi et al. 2019 ). Podophyllotoxin and its derivatives exhibit anticancer activity, mainly due to its ability to inhibit tubulin polymerisation into microtubules (Kamal et al.…”
Section: Discussionmentioning
confidence: 93%
“…Depending on the chosen modern molecule hybridization strategy [ 15 , 16 ], podophyllotoxin/epipodophyllotoxin can hybridize with amino acid/peptide [ 17 , 18 ], azole [ 19 ], biotin [ 20 ], carbamate [ 21 ], chalcone [ 22 ], cinnamic acid [ 23 ], cinnamic acid [ 24 ], ferrocene [ 25 ], furan/pyrrole [ 26 ], hydroxamic acid [ 27 ], indole [ 28 ], norcantharidin [ 29 ], pyridine/pyrimidine [ 30 ], pterostilbene [ 31 ], retinoic acid [ 32 ], sugar [ 33 ], (thio)urea [ 34 ], or sulfur [ 35 ] ( Figure 1 ). These have been subjected to extensive research and have been shown to be highly active against both MDR and drug-sensitive cancer cell lines with IC 50 or GI 50 values at a nanomolar level; however, the water solubility, bioactivities, and toxicity still need to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Geniposide from Gardenia jasminoides Ellis has potential applications in anticancer and antidepression therapeutics 3–5 . In addition, some studies have found that synthetic pyranoside derivatives of podophyllotoxin have more potent anticancer activity than podophyllotoxin itself and are currently lead compounds for the development of new anticancer drugs 6 . Thus, the screening and discovery of pyranosides not only contributes to research on natural products but may also promote pharmaceutical research and development.…”
Section: Introductionmentioning
confidence: 99%